2022
DOI: 10.1136/bmjopen-2021-059879
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mental health problems of Chinese front-line healthcare workers before, during and after the COVID-19 rescue mission: a qualitative study

Abstract: ObjectiveTo explore the physical and mental health problems of front-line healthcare workers fighting COVID-19 across the three phases of the epidemic rescue mission (before, during and after) in China.DesignA qualitative study was adopted using face to face, in-depth semistructured interviews. Phenomenological research methods and Colaizzi’s seven-step analysis method were used in the study.SettingThe setting of the study was the offices of healthcare workers in 12 tertiary hospitals.ParticipantsThirty-one fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In phase 3, for the BR‐PDS‐MRFE, the EFA supported one domain (i.e., anxiety), which explained 52.07% of the cumulative variance with factor loadings that ranged from 0.435 to 0.789. Previous studies have indicated that medical rescuers experience severe mental health problems including tension, fear, and hopelessness before arriving at the rescue scene (Li et al., 2020; Sun et al., 2022). Among those, the most common mental health problem was anxiety (Sun et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phase 3, for the BR‐PDS‐MRFE, the EFA supported one domain (i.e., anxiety), which explained 52.07% of the cumulative variance with factor loadings that ranged from 0.435 to 0.789. Previous studies have indicated that medical rescuers experience severe mental health problems including tension, fear, and hopelessness before arriving at the rescue scene (Li et al., 2020; Sun et al., 2022). Among those, the most common mental health problem was anxiety (Sun et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that medical rescuers experience severe mental health problems including tension, fear, and hopelessness before arriving at the rescue scene (Li et al., 2020; Sun et al., 2022). Among those, the most common mental health problem was anxiety (Sun et al., 2022). For the DR‐PDS‐MRFE, the EFA results found that six factors explained 69.75% of the cumulative variance, with factor loadings that ranged from 0.489 to 0.943.…”
Section: Discussionmentioning
confidence: 99%
“…However, healthcare workers are reported to be stigmatised by the public and face severe psychological and physical symptoms during quarantine. 42 Accordingly, some students may have wished to change their career goals. For university students in early adulthood (18–25 years old), the beginning of university study coincides with the transition stage of adulthood and independence; their minds are not yet mature.…”
Section: Discussionmentioning
confidence: 99%